THE INFLUENCE OF SERVICE QUALITY, CUSTOMER PERCEPTIONS, AND CUSTOMER INVOLVEMENT ON LOYALTY CUSTOMER WITH SATISFACTIONAN INTERVENING VARIABLE IN INDOMARET LHOKSEUMAWE CITY - T. Erna Setianingsih; Mohd. Heikal; Mariyudi; Khairina AR (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the influence of service quality, customer perception, and customer involvement on customer loyalty with customer satisfaction as an intervening variable at Indomaret, Lhokseumawe City. This research is categorized as quantitative. The population for this study consists of customer who have made more than one purchased at Indomaret, Lhokseumawe City. The sampling technique used is nonprobability sampling, specially convience sampling with a sample size of 125 respondents. The study involves three types of variables: the dependent variable (Y), the independent variable (X), and the intervening variable (Z). The dependent variable in this study is customer loyalty. The independent variables are service quality, customer perception, and customer involvement, while the intervening variable is customer satisfaction. The analysis methods employed include validity and reliability tests, classical assumption tests, simple and multiple linear regression analysis, path analysis, and sobel tests, with data performed using SPSS 29.0. The results show that service quality, customer perception, and customer involvement each have a positive and significant effect on customer loyalty. Additionally, customer satisfaction mediates the relationships between service quality and customer loyalty, customer perception and customer loyalty, and customer involvement and customer loyalty.